Towards a shared mental model of progressive competence in postgraduate medical education (Canadian Medical Education Journal, 2018)
Many professions have hierarchies and a promotion structure. Postgraduate medicine has a tradition of promoting residents based on time spent in a certain specialty. The military, too, may promote its personnel based on factors other than just merit. Both professions have been criticized for divorcing competence from promotion. While Competency-Based Medical Education (CBME) partly solves this problem in medicine, many models of CBME, including the Canadian one, retain distinct stages of training. We urgently need a shared mental model of what a learner in each stage looks like. Some models have been proposed but fall short.